The non-directive technique in play therapy its implication to the emotionally-disturbed children - Bitanga, Lolita S. 1948- (1976)
The study was undertaken to find out children's behavior, identify their personality characteristics and recommend the remedial measures to meet their needs. The subjects involved were eighty seven kindergarten pupils enrolled at Dr. A. Albert Elementary School, Manila in the year 1975. This study made use of the Bender Test, a projective testing instrument to identify the emotionally disturbed children. Out of the 87 pupils, 16 or 18 percent were found to be emotionally disturbed. Of the 16 or 18 percent, 10 or 23 percent are male and 6 or 13 percent are female. The researcher concluded that there are indications for the emotionally disturbed children and these are apparent. Boys tend to have more problems than girls.
Mimeographed.
Thesis (M.Ed.)--University of the Philippines, Quezon City.
Vita.
Keywords: Play therapy; Mentally ill children -- Care and treatment